Clinical evaluation of common allergens in contact dermatitis to cement - Narashimman, K.; Gomathi, V. (International Journal of Research in Dermatology, 2018)
Background: Cement is the most common cause of occupational dermatitis in construction industry. Skin contact with cement results in irritant contact dermatitis ranging from cement burns to chronic cumulative irritant contact dermatitis. Chromate, cobalt, nickel, epoxy resins and rubber chemicals are the important allergens in construction workers. The objective of the study was to study various clinical pattern of distribution and association between the duration of exposure to cement and clinical manifestation in occupational group. Methods: 107 cases of contact dermatitis with history of exposure to cement attending the occupational contact dermatitis outpatient department, Department of Dermatology, Rajiv Gandhi Government General Hospital and college, All the patients were subjected to blood investigation such as complete hemogram, liver function test, renal function test and absolute eosinophil count. Patient with history and clinical features suggestive of contact dermatitis due to cement were patch tested. Results: Among 107 patients, the most common pattern of involvement includes extremities which account for 64 patients (59.8%) Involvement of face, neck, trunk and extremities was seen in 11 patients (10.3%). Among 81 positive patch test patients, chromium was positive in 78 patients (96.3%) followed by epoxy resin in 14 patients 17.3% and cobalt and thiuram mix in 9 patients (11.1%) each and the least was black rubber mix in 3 patients (3.7%). Conclusions: This study emphasizes the need for standardization in the chrome content of cement. Strict workplace safety guidelines should be implemented from government to protect workers from developing contact dermatitis to cement.